Study of variability in antioxidant composition and fatty acids profile of Longissimus dorsi and Serratus ventralis muscles from Iberian pigs reared in two different Montanera seasons. - Tejerina, D; García-Torres, S; de Vaca, M Cabeza; Vázquez, F M; Cava, R (Meat science, 2012)
This investigation was designed to evaluate the effects of variations in antioxidant and fatty acids composition of acorns and grass from two Montanera (free-range system and feeding based on acorns and grass) seasons (2006/07 and 2007/08) on the antioxidant composition and fatty acids profile of m. Longissimus dorsi (LD) and m. Serratus ventralis (SV) from Iberian pigs reared under these Montanera seasons. Acorn and grass composition was affected by Montanera season and consequently, LD and SV muscles showed different contents of α-tocopherol, total phenols, hydrophilic and lipophilic antioxidant activity and fatty acid profile, according with the composition of acorns and grass ingested. Results suggest a lack of uniformity in meat quality between different seasons. This could be due to the variable nature of extensive pig production as reflected in the variability in the composition of the diet (acorns and grass).
Keywords: acorns; diet composition; Grass; Iberian pigs; meat; Montanera